Integrasi Hukum Pidana Islam dan Peradilan Umum Aceh: Tantangan & Solusi Penegakan Hukum - Lisma Wati (TERAJU: Jurnal Syariah dan Hukum, 2025)
This study aims to examine the integration of Islamic criminal law with the general judicial system in Aceh from a normative perspective, focusing on the challenges and solutions in law enforcement. Aceh is a region with special provisions in the implementation of Islamic criminal law, which simultaneously interacts with the general judicial system that applies in Indonesia. This research uses a normative approach by analyzing various laws, legal literature, and doctrines relevant to the integration of the two legal systems. The research findings indicate that normatively, the integration of Islamic criminal law and the general judicial system in Aceh presents several challenges, such as inconsistencies in the regulation of Islamic criminal law with existing positive law, differences in legal norms and procedures, as well as the lack of an effective system between the two. On the other hand, solutions that can be proposed include the formulation of more comprehensive regulations that govern the relationship between Islamic criminal law and the general judicial system, and the need for harmonization in the application of legal norms in accordance with justice principles. In conclusion, for the integration of Islamic criminal law with the general judicial system to function effectively in Aceh, clearer normative regulations and synchronization between the two legal systems are required to achieve the goal of fair and equitable law enforcement.